The prediction of quality of life based on personality traits and type of intelligence in women - Hossein Davudi; Hassanpasha Sharifi; Abdolah Shafiabadi; Valiyolah Farzad (روانشناسی و روانپزشکی شناخت, 2015)
Introduction: Recent studies of quality of life as what philosophers such as Plato, for centuries, has referred to the "good life" is defined. Objective: The goal of the present study was to investigate the prediction of the quality of life based on personality traits and the type of intelligence in women. Method: The research method was correlation. The population included all the married women in Markezi & Tehran provinces in 1914. 504 participants were chosen on the basis of cluster sampling. The tools of research were NEO questionnaire, cognitive, spiritual, emotional, moral, cultural intelligence questionnaires. Results: The results obtained from the analysis of the data showed that there was a significant positive relation between the quality of life and Extraversion, Agreeableness, Conscientiousness, Openness. Also there was a significant negative relation between the quality of life and Neuroticism . Also there was a significant positive relation between the quality of life and cognitive, spiritual, emotional, moral, cultural intelligences. Conclusion: According to the results of this study, knowledge of personality traits and the types of intelligence plays an important role in improving the quality of life.